Occupational sorting on genes - Thomas Buser; Rafael Ahlskog; Magnus Johannesson; Sven Oskarsson (Tinbergen Institute, 2023)
Are genetic differences between people associated with their career choices? We link data from a large sample of genotyped individuals to Swedish government register data on study major and occupation. Our data contains polygenic indices that summarize genetic variants linked to several components of human capital: cognitive skills, personality traits, mental health, and physical health. We present a detailed mapping of these genetic indices by occupation and study major. We show that differences in genes associated with human capital across careers are highly statistically significant. Rankings of majors and occupations differ strongly across indices, meaning that genes associated with different traits predict entry into different careers. Our results shed new light on the determinants of some of the most impactful decisions people must make in their lives.
Keywords: 330